Bladder trauma - (:unkn) unknown (Springer Berlin Heidelberg, 2007)
Traumatic injury to the bladder is relatively uncommon in adults as well as children. However, the incidence of blunt trauma is rising as a result of modern transportation preferences and increasing reliance on motor vehicles that travel at higher speeds in parallel with advances in engine and mobile parts technology. Therefore, the incidence of intraabdominal and bladder injuries can be expected to rise as well (Espinoza and Rodriguez 1997; Dobrowolski et al. 2002; McGahan et al. 2005). Also, domestic or professional accidents and violence of any sort, including terrorist activities, may contribute to the increasing frequency of intraabdominal and related bladder injury. © 2007 Springer-Verlag Berlin Heidelberg.